Understanding operating systems - McHoes, Ann McIver, 1950- (Course Technology/Cengage Learning, 2011)
This edition continues to provide a clear and straightforward explanation of operating systems theory and practice. The book's structure begins with a discussion of fundamentals before moving on to specific operating systems.